A global database for the distributions of crop wild relatives - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
This dataset originally held 5 647 442 total records, where 34% of the records corresponded to germplasm accessions and 66% to herbarium samples. A total of 3 231 286 records had cross-checked coordinates (see Figure 2). 322 735 records were newly georeferenced using The Google Geocoding API and 15 713 new records were obtained after digitizing the information contained in herbaria specimens. Data was gathered from more than 100 data providers, including GBIF (a comprehensive list of institutions and individuals is available here: http://www.cwrdiversity.org/data-sources/).The geographic coverage of the dataset includes 96% of the world countries and also includes records of cultivated plants (1/3 of the dataset). Records of the crop wild relatives of 80 crop gene pools can be queried and visualized in this interactive map: http://www.cwrdiversity.org/distribution-map/.For publication to GBIF, all records originally gathered from GBIF have been removed to avoid data duplication.